Characterization of Statin Low-Density Lipoprotein Cholesterol Dose-Response Using Electronic Health Records in a Large Population-Based Cohort. (September 2018) - Oni-Orisan, Akinyemi; Hoffmann, Thomas J.; Ranatunga, Dilrini; Medina, Marisa W.; Jorgenson, Eric; Schaefer, Catherine; Krauss, Ronald M.; Iribarren, Carlos; Risch, Neil
Abstract : Background: Low-density lipoprotein cholesterol (LDL-C) response to statin therapy has not been fully elucidated in real-world populations. The primary objective of this study was to characterize statin LDL-C dose-response and its heritability in a large, multiethnic population of statin users. Methods: We determined the effect of statin dosing on lipid measures utilizing electronic health records in 33 139 statin users from the Kaiser Permanente GERA cohort (Genetic Epidemiology Research on Adult Health and Aging). The relationship between statin defined daily dose and lipid parameter response (percent change) was determined. Results: Defined daily dose and LDL-C response was associated in a log-linear relationship (β, −6.17; SE, 0.09; P <10 –300 ) which remained significant after adjusting for prespecified covariates (adjusted β, −5.59; SE, 0.12; P <10 –300 ). Statin type, sex, age, smoking status, diabetes mellitus, and East Asian race/ethnicity were significant independent predictors of statin-induced changes in LDL-C. Based on a variance-component method within the subset of statin users who had at least 1 first-degree relative who was also a statin user (n=1036), heritability of statin LDL-C response was estimated at 11.7% (SE, 8.6%; P =0.087). Conclusions: Using electronic health record data, we observed a statin LDL-C dose-response consistent with the rule of 6% from prior clinical trial data. Clinical and demographic predictors of statin LDL-C response exhibited highly significant but modest effects. Finally, statin-induced changes in LDL-C were not found to be strongly inherited. Ultimately, these findings demonstrate (1) the utility of electronic health records as a reliable source to generate robust phenotypes for pharmacogenomic research and (2) the potential role of statin precision medicine in lipid management. Abstract : Supplemental Digital Content is available in the text.